Questões de gênero em materiais didáticos de português como língua adicional - Almeida, Adrielly Carine da Cruz (2023)
Discussions related to gender issues (grammatical, social, orientation) have been increasingly frequent in different contexts of action, due to the need to adapt to the inclusion of all people. Likewise, studies related to the teaching and teaching materials of Portuguese as an Additional Language have been frequent, since globalization, migrations and the interest in Portuguese have increased the contact zone with Portuguese-speaking people and culture. In this sense, this dissertation aims to interpret the way gender is presented in two Portuguese textbooks for foreigners, based on the identification of linguistic markers. The guiding questions were: (1) How do Portuguese as an Additional Language (PLA) textbooks present their content related to gender identity?; (2) Is there a difference in the presentation of gender issues in the two didactic materials and, if so, which ones?; and (3) How do such notions impact learners' perceptions of their identification processes in Portuguese?. Therefore, methodologically, this dissertation proposes a comparative analysis between two Portuguese textbooks for foreigners, namely: Novo Avenida Brasil 1 and Plural: Português Pluricêntrico, which were produced in different contexts. The comparative analysis was carried out based on notions about gender studies and reflection on how the treatment of gender identities in textbooks can impact teaching. To carry out the research, the qualitative method was used, since social meanings were researched and discussed. The analysis showed that there is a difference in the composition of the two teaching materials, since, by excluding gender relations in a learning environment, the learner is limited in relation to the knowledge that could be obtained.